(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the value of Rajan’s Heart Failure (R-hf) score in predicting 3-month cardiovascular outcomes (CVOs) in patients with acute decompensated heart failure (ADHF). Methods: A combined prospective and retrospective cohort study was conducted on 233 patients (median age: 67 years; 52.9% female) hospitalized for ADHF. The R-hf score was calculated by multiplying the estimated glomerular filtration rate (eGFR, mL/min/1.73m²), left ventricular ejection fraction (LVEF, %), and hemoglobin level (g/dL), then dividing by NT-proBNP levels (pg/mL). Risk categories were stratified as very low (≥50), low (≥10 to <50), intermediate (≥5 to <10), and high (<5). CVOs included all-cause mortality and rehospitalization due to ADHF within 3 months. Results: The CVO rate was 22% (n=49), including 3.1% mortality and 18.8% rehospitalization. The median R-hf score was significantly higher in patients without CVOs compared to those with (7.8 vs. 1.7 points, p<0.001). CVO rates increased across risk categories: very low 0%, low 6.6%, intermediate 18%, and high 34.3% (p<0.001). An R-hf score <2.25 demonstrated good predictive ability with an AUC of 0.823 (95% CI: 0.758–0.887), sensitivity of 69.4%, specificity of 85.6%, positive predictive value of 57.6%, and negative predictive value of 90.8%. Conclusion: The R-hf score had high predictive value for 3-month CVOs in patients with ADHF, providing an effective tool for risk stratification and guiding patient management.